Development of the concept of building project management systems in the context of digital transformation of project-oriented companies - Teslia, Iurii; Khlevna, Iulia; Yehorchenkov, Oleksii; Yehorchenkova, Nataliia; Grigor, Oleg; Kataieva, Yevheniia; Latysheva, Tatiana; Prokopenko Tеtiana; Tryus, Yuriy; Khlevnyi, Andrii (Eastern-European Journal of Enterprise Technologies, 2022)
An analysis of the impact of new global trends, such as Industry 4.0, on project-oriented companies was performed. Based on the analysis, the research problem is formulated, which consists in the need to create project management systems in accordance with the concepts, ideas, principles and methods of digital transformation of project-oriented companies. Project management processes in the conditions of digital transformation of project-oriented companies are defined as the object of research. An approach to the creation of project management systems is proposed, which is based on the need to adapt the organizational, methodological and technological components of these systems to the specifics of a project-oriented company and the conditions of digital transformation. Based on this approach, the methodological, organizational and technological components of project management systems were improved. As part of the organizational component, a structural and functional model of project management is proposed, which takes into account the conditions of digital transformation of a project-oriented company. Within the framework of the methodological component, it is proposed to use management meta-methodology to create a project management methodology specific to the company’s conditions and digital transformation processes. A digital interpretation of matrix information technologies for the technological component is proposed. An organizational and technological model of implementation of project management systems in the conditions of digital transformation of companies was developed. The conditions for the practical use of the concept are given: the systematic organization of the digital space and the availability of qualified specialists in the creation of project management systems. The implementation of the concept made it possible to reduce the project execution time by 5–20 %, as well as project cost due to more rhythmic work performance